Quality research in nursing - Stychno, Ewa; Kulczycka, Kinga (Nursing in the 21st Century, 2011)
The article aims to show the essence of quality research in nursing. Conducting this type of research requires the researcher to possess knowledge concerning the way it is carried out, as well as the subject of study.The person who decides to put the quality research into practice must:– understand its meaning and essence,– possess knowledge of oneself about the assumptions with which they start the research,– know the subject of studyQuality research require specific conditions of the methodological correctness.